Balkan and Mediterranean candidates for European Union membership: The convergence of their monetary policy with that of the European Central Bank - Josef C. Brada; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
We compare the convergence with German monetary policy of the Balkan and Mediterranean country candidates for EU membership with that of countries that have recently joined the EU. Significant linkages exist between German base money stock and that of recent members of the EU; the same holds true for some of the Mediterranean region candidates for EU membership and for Slovenia and Croatia. Among the other Balkan economies and Turkey, the ability to follow the policies of the Bundesbank is nonexistent. Such weak policy coordination suggests the need for strengthening the financial sectors of these countries, for macroeconomic stabilization and for a period in which they tie their policies more closely to the ECB before they can be considered serious candidates for EU membership.
Keywords: E58; F15; F36; P52; 330; convergence; economic integration; monetary policy; transition economies; EU-Erweiterung; Geldpolitik; Internationale wirtschaftspolitische Koordination; Geldbasis; Schätzung; De